2018
DOI: 10.1016/j.envint.2017.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Associations between long-term PM2.5 and ozone exposure and mortality in the Canadian Census Health and Environment Cohort (CANCHEC), by spatial synoptic classification zone

Abstract: Studies suggest that long-term chronic exposure to fine particulate matter air pollution can increase lung cancer mortality. We analyzed the association between long term PM and ozone exposure and mortality due to lung cancer, ischemic heart disease, and chronic obstructive pulmonary disease, accounting for geographic location, socioeconomic status, and residential mobility. Subjects in the 1991 Canadian Census Health and Environment Cohort (CanCHEC) were followed for 20years, and assigned to regions across Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 52 publications
2
68
1
Order By: Relevance
“…Twelve studies ( Crouse et al, 2015a , Lipsett et al, 2011 , Weichenthal et al, 2017 , Turner et al, 2016 , Lipfert et al, 2006 , Lipfert et al, 2006 , Bentayeb et al, 2015 , Cakmak et al, 2018 , Di et al, 2017 , Krewski et al, 2009 , Smith et al, 2009 , Cakmak et al, 2016 ) reported the association between warm season O 3 exposure and all-cause mortality. Seven studies ( Lipsett et al, 2011 , Weichenthal et al, 2017 , Turner et al, 2016 , Lipfert et al, 2006 , Bentayeb et al, 2015 , Cakmak et al, 2018 , Di et al, 2017 ) with most recent cohort results were included for pooled analysis ( Table 3 a). Meta-analysis result showed that a 10 μg/m 3 increase in O 3 exposure was associated with a RR of 1.01 (1.00, 1.02) per 10 μg/m 3 for all-cause mortality although the heterogeneity was high among studies (I 2 = 98%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies ( Crouse et al, 2015a , Lipsett et al, 2011 , Weichenthal et al, 2017 , Turner et al, 2016 , Lipfert et al, 2006 , Lipfert et al, 2006 , Bentayeb et al, 2015 , Cakmak et al, 2018 , Di et al, 2017 , Krewski et al, 2009 , Smith et al, 2009 , Cakmak et al, 2016 ) reported the association between warm season O 3 exposure and all-cause mortality. Seven studies ( Lipsett et al, 2011 , Weichenthal et al, 2017 , Turner et al, 2016 , Lipfert et al, 2006 , Bentayeb et al, 2015 , Cakmak et al, 2018 , Di et al, 2017 ) with most recent cohort results were included for pooled analysis ( Table 3 a). Meta-analysis result showed that a 10 μg/m 3 increase in O 3 exposure was associated with a RR of 1.01 (1.00, 1.02) per 10 μg/m 3 for all-cause mortality although the heterogeneity was high among studies (I 2 = 98%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies reported the warm season O 3 exposure with COPD mortality ( Table 3 c). Turner 2016 ( Turner et al, 2016 ) showed that increased O 3 exposure was associated with higher risk of COPD mortality, while Cakmak 2018 ( Cakmak et al, 2018 ) found no significant association between O 3 exposure and COPD mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Indoor and outdoor air pollution has been deemed as a significant contributor for lung cancer, especially for lung adenocarcinoma and female patients; additionally, it might play a role in the observed urban-rural disparity of lung cancer in Taiwan [26]. e exposure-response relationship was demonstrated by several large cohorts where each 10 μg/ m 3 increase in the ambient PM 2.5 concentration was correlated with an increased risk of lung adenocarcinoma (hazard ratio 1.31; 95% CI � 0.87-1.97) in nonsmokers and an additional 15-27% risk of lung cancer mortality in lifelong never-smokers [26][27][28]. Former smokers had an additional risk of lung cancer in association with outdoor particular matter exposure compared with never-smokers [29].…”
Section: Discussionmentioning
confidence: 97%
“…Long-term exposure has been linked to premature respiratory mortality in adults [ 69 ] and to increased risk of death in susceptible populations with chronic cardiopulmonary diseases and diabetes [ 70 ]. Less evidence is available for an association between ozone and lung cancer, with one Canadian study finding an odds ratio for lung cancer incidence of 1.09 (0.85–1.39) with a 10-U increase in ozone [ 71 ] and another Canadian study found ozone was a non-significant contributor to lung cancer mortality [ 72 ].…”
Section: Methodsmentioning
confidence: 99%